The role of parents in motivating children's learning in the family environmen NGESREP Village banyumanik district, semarang City : The role of parents in motivating children's learning in the family environmen NGESREP Village banyumanik district, semarang City - Belum berkeluarga, Ristanovi Widiyanti; Ismanto, Heri Saptadi; Ajie, G Rohastono (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2024)
ABSTRAK Apart from the teaching and learning process at school, the role of parents influences students' success in learning. During the learning process at home, the role of parents is really needed as a substitute for the teacher at home in guiding their children and as a motivator during the distance learning process. This type of research is qualitative field research, namely: research procedures in the form of written and spoken words from people and the observable behavior of informants. The subjects of this research were children of parents who were motivated to learn. Data collection uses interviews and documentation. Data analysis uses descriptive analysis with triangulation techniques. The results of the research show that what parents do to increase children's learning motivation is by encouraging children's learning motivation, giving attention to children, providing learning facilities in a comfortable place for children, giving gifts or appreciating children's learning outcomes and knowing the results of learning achievements child. Keywords: The role of parents, learning motivation, family environment